Baseline serum EV-miR-1-3p as a protective factor and biomarker for hepatocellular carcinoma development after HCV eradication - Wei Teng; Wei-Ting Ku; Po-Ting Lin; Guan-Ting Chen; LiChieh Julie Chu; Hsuan Liu; Yung-Chang Lin; Chun-Yen Lin (Journal of Translational Medicine)
Abstract Background Direct-acting antiviral (DAA) therapy for chronic hepatitis C (CHC) achieves high sustained virologic response (SVR) rates; however, hepatocellular carcinoma (HCC) can still develop after viral eradication. Reliable biomarkers for predicting the post-SVR HCC risk are lacking. This study aimed to identify baseline serum extracellular vesicle microRNAs (EV-miRNAs) associated with HCC development following SVR. Materials and methods Eleven CHC patients who achieved SVR were retrospectively enrolled as a discovery cohort to identify candidate EV-miRNAs at SVR12 predictive of future HCC. An independent validation cohort of 89 CHC patients was also analyzed. HCC development was defined as the occurrence of HCC at ≥ 12 months after SVR. EV-miRNA profiles were assessed by small RNA sequencing and validated using a miRNA enzyme immunoassay (miREIA). Results In the discovery cohort, four EV-miRNAs (EV-miR-1-3p, EV-miR-148a-3p, EV-miR-223-3p, and EV-miR-4433b-5p) were significantly different between patients who later developed HCC and those who remained HCC-free at SVR12. In the 89-patient validation cohort, 51 (57.3%) developed HCC with a median disease-free survival (DFS) of 23.1 months, and 12 (13.5%) patients died during a median follow-up of 77 months. High baseline EV-miR-1-3p and EV-miR-148a-3p levels and low EV-miR-4433b-5p were associated with remaining HCC-free. Elevated EV-miR-1-3p and EV-miR-148a-3p levels were also correlated with longer DFS (p < 0.05). In multivariate analysis, EV-miR-1-3p was the only independent predictor of longer DFS (adjusted hazard ratio [HR] 0.459, p = 0.014) and improved overall survival (OS) (adjusted HR 0.390, p = 0.016) after SVR12. Among all biomarkers evaluated, baseline EV-miR-1-3p demonstrated the highest predictive accuracy for HCC occurrence (area under the curve [AUC] 0.843, vs. 0.769 for alpha-fetoprotein [AFP] and 0.755 for FIB-4; p < 0.001) and for OS (AUC 0.876, vs. 0.480 for AFP and 0.655 for FIB-4; p < 0.001). Furthermore, patients with high EV-miR-1-3p levels showed higher platelet counts and albumin, and a lower proportion with FIB-4 ≥ 3.25, suggesting that high EV-miR-1-3p reflects better preserved liver function and less advanced fibrosis. Conclusions Baseline serum EV-miR-1-3p serves as a protective biomarker for stratifying HCC risk and predicting survival in CHC patients after HCV eradication via DAA therapy.